1991
DOI: 10.2337/diab.40.2.s115
|View full text |Cite
|
Sign up to set email alerts
|

Islet Function in Offspring of Mothers on Low-Protein Diet During Gestation

Abstract: A low-protein diet (8 vs. 20%) administered during pregnancy affects the structure and function of the endocrine pancreas of the offspring. At 21.5 days of gestation, we reported a reduction of cell proliferation, islet size, islet vascularization, and pancreatic insulin content. In this study, we demonstrated an impairment of insulin secretion of these fetal islets when stimulated in vitro with amino acids such as arginine and leucine. If the offspring is kept on the same low-protein diet during suckling, wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
284
3
6

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(304 citation statements)
references
References 0 publications
9
284
3
6
Order By: Relevance
“…The early period (days 0-7) corresponds to the embryonic phase of development in the rat and in fact embryos only implant at around day 4.5. 7 The mid-gestation period (days [8][9][10][11][12][13][14] largely corresponds to the period of organogenesis, while late gestation (days [15][16][17][18][19][20][21][22] is the period of most rapid growth and differentiation of key structures. By feeding at these targeted periods, it is possible to identify when nutritional programming occurs and this can provide important indicators of potential mechanisms.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The early period (days 0-7) corresponds to the embryonic phase of development in the rat and in fact embryos only implant at around day 4.5. 7 The mid-gestation period (days [8][9][10][11][12][13][14] largely corresponds to the period of organogenesis, while late gestation (days [15][16][17][18][19][20][21][22] is the period of most rapid growth and differentiation of key structures. By feeding at these targeted periods, it is possible to identify when nutritional programming occurs and this can provide important indicators of potential mechanisms.…”
Section: Animalsmentioning
confidence: 99%
“…A large number of studies in rats, mice, guinea pigs and sheep have clearly shown that exposure to relatively short periods of undernutrition or endocrine disturbance in fetal life can programme raised blood pressure, glucose intolerance and insulin resistance. [7][8][9] The range of nutritional exposures capable of eliciting programmed responses in the developing offspring is broad, including micronutrient deficiency, [10][11][12] excess of saturated fat 13 and restriction of food intake (global nutrient restriction). 14,15 In the present paper, we report findings from a model of low protein feeding in rat pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review study suggested that inadequate maternal nutrition might disturb the development of the fetus, which must adopt strategies to ensure survival that will programme its future health [3]. In experimental animal models, alteration of the intrauterine environment induced, for example, by gestational diabetes [4], placental insufficiency [5,6] or poor maternal nutrition [7][8][9][10][11] compromise the development of endocrine pancreas in the progeny and impact on its future health even in the subsequent generation [4,6,12]. Reduction of food intake by 50% in rats during gestation reduced the beta cell mass in offspring at birth by 30% [9].…”
Section: Introductionmentioning
confidence: 99%
“…When maternal diet was reduced in protein content during gestation, a number of findings were observed: reduction in beta cell mass due to diminished proliferation [8,13], enhanced apoptosis [11,13], reduced insulin secretion in vitro from isolated islets [14], impaired islet vascularisation [8,15] and enhanced sensitivity to cytotoxic effects of cytokines in vitro [11]. Increased susceptibility to cytokine cytotoxicity and lower insulin secretion persisted in adulthood despite limiting the low-protein (LP) diet to the period of gestation and lactation [7,12]. Maternal and fetal plasma glucose levels were not altered by maternal malnutrition, but the plasma amino acid profile was perturbed both in the mother and their fetuses [16].…”
Section: Introductionmentioning
confidence: 99%
“…In this model, a low-protein (LP) diet (8% vs 20% control) given during gestation leads to offspring having lower body weight. Pancreatic beta cell mass, insulin content and insulin secretion are reduced at birth [2,3]. In addition, in vivo and in vitro, the proliferation rate of fetal islet cells is lower [2,4,5,6], while apoptosis is higher [5,6,7].…”
Section: Introductionmentioning
confidence: 99%